Implementasi Push Notifikasion Berbasis Android Untuk Sistem Monitoring Keamanan Rumah - Siddik, Mohd. (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Monitoring the security of the house is something that needs to be done to prevent criminals. Housing is a very important thing for us to be aware of, where most of the perpetrators of crime occurred in homes that were left traveling by the occupants. Therefore, for the sake of comfort when we travel, monitoring the state of the house is very necessary. In this monitoring system is done by monitoring the doors and windows of the house using a magnetic switch sensor, later each sensor on the door and window will be connected to the Raspberry Pi which is synchronized with firebase, and every door or window that is open the sensor will send information to Firebase. and then by utilizing push notification firebase will send notification messages to the android application that has been designed. With this, residents monitor the state of the house when traveling using an android application that has been designed via a smartphone, where every open door and window will be visible on the android application display. Using this monitoring system can create a sense of comfort and safety for residents when traveling.